Validation of Reference Genes for Quantitative Real-Time PCR during Bicolor Tepal Development in Asiatic Hybrid Lilies (Lilium spp.) - Xu, Leifeng; Xu, Hua; Cao, Yuwei; Yang, Panpan; Feng, Yayan; Tang, Yuchao; Yuan, Suxia; Ming, Jun (Frontiers in Plant Science, 2017)
Quantitative real-time PCR (qRT-PCR) is a reliable and high-throughput technique for gene expression studies, but its accuracy depends on the expression stability of reference genes. To date, several reliable reference gene identifications have been reported in Lilium spp., but none has been obtained for lily tepals at different developmental stages. In this study, ten candidate reference genes were selected and evaluated for their expression stability in Lilium ‘Tiny Padhye’ during the process of bicolor tepal development. The expression stability of these candidates was evaluated by three software programs (geNorm, NormFinder, and BestKeeper) and the comparative ΔCt method, and comprehensive stability rankings were generated by RefFinder. As a result, TIP41-like family gene (TIP41) and actin (ACT) were the best combination of reference genes for tepals at different developmental stages; TIP41 and F-box family gene (F-box) for tepals under shading treatment; ACT, actin11 (ACT11), and elongation factor 1-α (EF1-α) for different tissues; and ACT, TIP41, and ACT11 for all samples. The selected optimal reference genes were further verified by analyzing the expression levels of flavonoid 3′-hydroxylase (LhF3′H) and anthocyanidin 3-O-glucosyltransfersae (LhUFGT) in tepals at different developmental stages. This study provides useful information for gene expression characterization in lilies under different experimental conditions, and can serve as a basis for similar research in other closely related species.